Beyond protein structure determination with MicroED. (October 2020) - Nguyen, Chi; Gonen, Tamir
Abstract : Microcrystal electron diffraction (MicroED) was first coined and developed in 2013 at the Janelia Research Campus as a new modality in electron cryomicroscopy (cryoEM). Since then, MicroED has not only made important contributions in pushing the resolution limits of cryoEM protein structure characterization but also of peptides, small-organic and inorganic molecules, and natural-products that have resisted structure determination by other methods. This review showcases important recent developments in MicroED, highlighting the importance of the technique in fields of studies beyond protein structure determination where MicroED is beginning to have paradigm shifting roles.